PASAR MODAL SYARIAH - Syifa Destya Salsabila; Burhanudin; Putri Amanda Ardita; Fifi Aprilia Yulianti; Ria Anisatus Solihah; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
This research aims to find out about the sharia capital market. This research method uses a literature study approach sourced from books according to the topic and focuses on research. The results of the literature review in this research conclude that the Islamic capital market is a capital market whose entire activity mechanism, especially regarding issuers, the types of securities traded and the trading mechanism is in accordance with sharia principles. The capital market or stock exchange has been around since the Dutch colonial era and to be precise in 1912 in Batavia. The capital market plays a role in carrying out two functions simultaneously, namely an economic function and a financial function. Legal entities in carrying out sharia capital market activities are regulated by Bapepam-Lk.